Effect of Testicular Sperm Extraction Outcome on Sexual Function in Patients With Male Factor Infertility - ŞİMŞEK, FERRUH (ELSEVIER SCIENCE INC, 2010)
OBJECTIVES To document the effects of the outcome of testicular sperm extraction (TESE) procedures on erectile function in patients with male factor infertility. METHODS A total of 66 nonobstructive azoospermic patients were divided into 2 groups: group I, with sperm-positive results and group II, with sperm-negative results. The patients were evaluated with the International Index of Erectile Function-5 (IIEF-5) and Hospital Anxiety-Depression Scale. Hormones were analyzed before and 6 months after the procedure. Each group was compared with the use of the paired t test, where P <.05 was accepted as statistically significant. RESULTS The mean patient age was 34.8 years (range 24-53). Of 66 cases, 26 (40%) experienced positive results for the TESE. The median IIEF-5 score before TESE for group I and group II was 22 ( minimum: 11, maximum: 25) and 23 (minimum: 10, maximum: 25), respectively. The median IIEF-5 score after TESE for group I and group II was 23.5 (minimum: 10, maximum: 25) and 18 ( minimum: 15, maximum: 25), respectively. In patients who reported new onset erectile dysfunction (ED) 6 months after surgery, the mean follicle-stimulating hormone and luteinizing hormone levels increased from 21 +/- 2 to 38 +/- 3 IU/L (P <.001), and from 11 +/- 2 to 14 +/- 2 IU/L (P >.05), respectively. The mean total testosterone level decreased from 7.83 +/- 2 to 2.8 +/- 2 ng/mL (P <.001). The Hospital Anxiety and Depression Scale revealed that patients who reported new onset ED also reported both depression and anxiety. CONCLUSIONS Unsuccessful TESE procedures might have a negative effect on erectile function because of hormonal and psychological reasons. The andrologist should treat the ED of the patients and refer them to the psychiatrist for anxiety and depression assessment. UROLOGY 75: 598-602, 2010. (C) 2010 Published by Elsevier Inc.
Keywords: NONOBSTRUCTIVE AZOOSPERMIA; TESTOSTERONE THERAPY; ERECTILE DYSFUNCTION; ANXIETY; MEN; INJECTION